Less is more: Removing a modality of an expected olfactory-visual stimulation enhances brain activation - Schicker, Doris; Blankenagel, Sonja; Zimmer, Claus; Hauner, Hans; Freiherr, Jessica (Human Brain Mapping, 2022)
In recent years, multisensory integration of visual and olfactory stimuli has extensively been explored resulting in the identification of responsible brain areas. As the experimental designs of previous research often include alternating presentations of unimodal and bimodal stimuli, the conditions cannot be regarded as completely independent. This could lead to effects of an expected but surprisingly missing sensory modality. In our experiment, we used a common functional magnetic resonance imaging (fMRI) study design with alternating strong unimodal and bimodal olfactory-visual food stimuli, in addition to a slight overhang of the bimodal stimuli in an effort to examine the effects of removing a visual or olfactory congruent stimulus for older people (41–83 years). Our results suggest that the processing of olfactory and visual stimuli stays intact over a wide age-range and that the utilization of strong stimuli does not lead to superadditive multisensory integration in accordance with the principle of inverse effectiveness. However, our results demonstrate that the removal of a stimulus modality leads to an activation of additional brain areas. For example, when the visual stimulus modality is missing, the right posterior superior temporal gyrus shows higher activation, whereas the removal of the olfactory stimulus modality leads to higher activation in the amygdala/hippocampus and the postcentral gyrus. These brain areas are related to attention, memory, and the search of the missing stimulus. Consequently, careful attention must be paid to the design of a valid, multimodal sensory experiment while also controlling for cognitive expectancy effects that might confound multimodal results.
CRIS-Team Scopus Importer:2022-02-25
Keywords: expectations; fMRI; multisensory; olfaction; stimulus removal; vision